O-002 Incidence and predictors of woven endobridge (WEB) compaction following treatment of intracranial aneurysms in a large multicenter study. (23rd July 2022) - Adeeb, N
Abstract : Introduction: In recent years, there was a rising concern for increased rate aneurysm recanalization and retreatment following Woven EndoBridge (WEB) embolization due to device compaction. This phenomenon corresponds to a decrease in WEB height leading to aneurysmal recanalization. A better understanding of WEB compaction and its predisposing factors can potentially lead to higher aneurysm occlusion rates. Objectives: We aim to investigates the compaction rate of implanted WEB devices and the factors associated with this phenomenon. Methods: A retrospective analysis of the WorldwideWEB Consortium, a synthesis of prospectively maintained databases at 22 academic institutions in North America, South America, and Europe, was performed to identify patients with intracranial aneurysms treated with WEB device. Only adult patients (age >18 years) patients with available aneurysm measurements, imaging follow-up, and compaction rate were included in this study. Both ruptured and unruptured aneurysms in all locations were included. Device compaction was classified into no compaction, minor compaction (<50%), and major compaction (>50%). Results: A total of 405 patients (mean age 60 years; male:female ratio 1:2.8) met the inclusion criteria for this study. A ruptured aneurysm was present in 22.7% of patients. In the present study, minor compaction (<50%) and major compaction (>50%) were encountered in 31.4% and 10.1% of aneurysms, respectively. The degree of compaction correlated inversely with the rate of adequate aneurysm occlusion at latest available follow-up as follows: 90.3% of aneurysms with no device compaction had adequate occlusion, compared to 78.9% in those with minor compaction and 70.7% with major compaction (p < 0.001). A direct correlation was found between device compaction and aneurysm retreatment rate, as 5.1% retreatment rate with no compaction, 13.7% with minor compaction, and 26.8% with major compaction (p < 0.001). On multivariable analysis, incomplete immediate aneurysm occlusion (p = 0.02) and a difference between aneurysm maximum width minus WEB width of >0.0 mm (p = 0.04, figure 1 ) were independent predictors of major compaction at last follow-up. Conclusion: WEB device compaction inversely correlates with aneurysm occlusion rate and directly with recanalization and retreatment. Using a device that is equal in width or oversized by 1–2 mm in relation to the aneurysm maximum width led to a significantly lower rate of major compaction. Immediate aneurysm occlusion by the end of procedure also showed a significant correlation with WEB compaction at last follow-up. Disclosures: N. Adeeb: None.